Crisis at the crossroads: Climate, peace, and security in the Sahel - Fatimata, Kone (2024)
The Sahel is at the heart of a crisis exacerbated by extreme climatic conditions, which amplify intercommunal conflicts and accelerate population displacements. This region, encompassing countries like Mali and Burkina Faso, is particularly vulnerable to climate change due to its reliance on rain-fed agriculture and limited natural resources. In a concerted effort to address these pressing issues, key organizations such as the United Nations Development Programme (PNUD), the Integrated Development Authority for the Liptako-Gourma region (ALG), and the CGIAR have collaborated to bolster national climate security efforts across the region.